Efficient Material Handling: A Novel Adaptive Gating System for Small and Irregular Parts - Mohan Arumugam; Arumugam, Prabukarthi; Mayilswamy, Suresh; Sadasivam, Udhayakumar (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
In the automotive industry, efficient handling of small and irregular components is imperative for production optimization. Traditional methods involving labor or robotic systems can lead to increased costs. The research introduces an innovative, dynamic gating system, integrating a camera module with computing intelligence to process images and orient parts effectively in linear feeders. Theoretical and experimental results validate the most preferred orientation, with orientations 1 and 2 from group 1 identified as the optimum resting positions. The use of both the Markov model and a hidden Markov model in trap module design yields a robust outcome, effectively attaining the necessary part orientation. The dynamic part feeding system is optimized for frequencies of 45 and 50 Hz with trap angles of 30° from the experimental study. The study quantifies efficiency gains, demonstrating that the proposed system outperforms manual or robotic methods. This study offers a quantitative and comprehensive solution for assembling and packaging small and irregular components in the automotive sector.